The GWCT Partridge Count Scheme: A Volunteer-Based Monitoring and Conservation Promotion Scheme - Julie Ewald; Nevile Kingon; Hugues Santin-Janin (National Quail Symposium Proceedings, 2017)
The Game & Wildlife Conservation Trust’s (GWCT) Partridge Count Scheme (PCS) is a volunteer-based monitoring system serving as a means for delivering conservation and ‘best practice’ advice to participants (farmers, land managers and gamekeepers). Originally designed to monitor numbers of grey partridge (Perdix perdix) on UK shooting estates, it has been expanded to include participants primarily interested in conservation in response to the UK government’s Grey Partridge Species Action Plan. The PCS is also an invaluable tool for examining trends in partridge abundance and population parameters. We examined trends in annual Grey Partridge production (autumn counts available from 1933) and breeding abundance (spring counts available from 1952). We compared trends of production and breeding abundance from old participants to trends from recently joined participants and interpreted the results relative to the Grey Partridge Species Action Plan. We also discuss the provision of data back to PCS participants and future plans for conservation advice and collaboration with other organizations, in particular the UK government’s Department for the Environment, Farming and Rural Affairs.
Keywords: gray partridge; Partridge Count Scheme; Perdix perdix; UK